Influence of incubation temperature on emu (dromaius novaehollandiae) egg hatchability - KUMAR, P SENTHIL; JAGATHEESAN, P N RICHARD; ANANDH, M ANNA; RAJARAJAN, G; PARAMASIVAM, A (The Indian Journal of Animal Sciences, 2012)
The study was conducted to assess an effect of incubation temperature (97.5° F, 98.0° F and 98.5° F) on hatching performance of emu eggs. A total of 150 eggs were divided into 3 equal groups (1, 2 and 3) differing in the incubation temperature (97.5° F, 98.0° F and 98.5° F in dry bulb respectively). Significant differences between the groups were observed for dead in shell. Raising the temperature to 98°F in G 2 and 98.5° F in G 3 led to reduce hatchability indices, primarily due to an increased rate of embryonic mortality found in both groups. Significantly different (P<0.05) mean±SE % of total egg hatchability and fertile egg hatchability were observed for G I, G 2 and G 3, respectively. The mean±SE incubation period (days) were 50.11±0.66, 49.87±0.12 and 49.77±0.13 for G 1, G 2 and G 3, respectively. The shortest incubation period recorded in this study was 49.77 days (G 3) at highest incubation temperature (98.5° F), while highest incubation period was 50.11 days at lowest incubation temperature (97.5° F). A reversed trend was observed in hatching time, which expanded, in G 2 and G 3, compared with G 1. From this study, it can be concluded that the best hatching performance was achieved at 97.5°F (G1) incubation temperature. Application of higher incubation temperature led to increased % of dead embryos, decreased hatchability, shortened the duration of artificial incubation and increased hatching duration.